Dendritic cells, indoleamine 2,3 dioxygenase and acquired immune privilege - Huang, Lei (2010)
Dendritic cells (DCs) are specialized to stimulate T cell immunity. Paradoxically some DCs suppress T cell responses, and activate regulatory T cells. In this review we focus on a potent counter-regulatory pathway mediated by plasmacytoid DCs (pDCs) expressing the immunosuppressive enzyme indoleamine 2,3 dioxygenase (IDO). IDO-expressing pDCs inhibit effector T cell responses, activate regulatory T cells, and attenuate pro-inflammatory responses in settings of chronic inflammation that manifest in clinical syndromes such as infectious, allergic and autoimmune diseases, cancer, and transplantation. Thus IDO-expressing pDCs create immune privilege, and provide novel opportunities to improve immunotherapy in multiple disease syndromes.